Temperature monitoring system - Mohd Azizul, Ghafur Rahimi (2008)
Temperature monitoring system has become very famous method in engineering field these days to monitor any types of break down, system failure and overheating. Global warming that heat the world these days makes temperature monitoring system not only relevant and important in engineering field, but also in domestic house usage. House Temperature Monitoring System was the other system that very crucial these days in monitoring temperature in the house especially in area below roof and above ceiling where heat always cumulate. The purpose of this project is to monitor temperature that cumulate in the stated area above that determines the overall temperature in the house. For the additional in this project, this monitoring system will also be equipped with fan that will active at certain temperature, will channel out hot air in the area inside the roof compartment. This action will allow little cold air enter the roof compartment and replace the hot air that will keep the temperature of air stabilized at certain temperature. Because this system is equipped with RF transmitter and receiver, user can monitor the temperature in roof compartment by referring to receiver part of the system that being installed in the area that easy to reach by user. This system being design so it will updates the temperature continuously in very short time. Hence, the circuit design must consist of RF module, PIC microchip, temperature sensor, fan(as the small project it will used DC motor) and also LCD to display the output. There will be two hardware been constructed for this project which called transmitter board and receiver board. Both of hardware must have main control panel such as microcontroller or other microprocessors to ensure all the process in both side run smoothly.